UK kidney association clinical practice guideline: update of anaemia of chronic kidney disease - Sunil Bhandari; Sebastian Spencer; Ben Oliveira; Ashraf Mikhail; Owain Brooks; Gareth Bryant; Michelle Willicombe; Richard Baines; Louise Alldridge; Sally Haslam-England (BMC Nephrology)
Abstract Anaemia is common in chronic kidney disease (CKD) encompassing non-dialysis dependent CKD (NDD-CKD) and dialysis dependent CKD (DD-CKD); people on peritoneal dialysis (PD) and haemodialysis (HD); and kidney transplant recipients (KTR). Iron deficiency and erythropoietin deficiency are the most common causes of anaemia in people with CKD, especially those requiring kidney replacement therapy (KRT). The Renal National Service Framework and National Institute for Health and Clinical Excellence in the UK, and Kidney Disease Improving Global Outcomes (KDIGO), all advocate treatment of anaemia in people with CKD. Blood transfusions are infrequently required, and newer therapies such as Hypoxia-Inducible Factor (HIF-PHI) stabilisers are now in current use. This guideline provides evidence based graded practice guidance on the use of iron; comments on iron deficiency without anaemia in people with CKD; provide further information on anaemia management in people with a transplant and provide guidance in the use of the new HIF-PHI drugs. It also provides audit and research recommendations.